Comparative Study of Students' Motivation in Learning Biology between Private Schools in Urban and Rural Areas - Raja, Nova Riama Lumban; Sasono, Tjatur Imbang (Universal Education, 2024)
This study compares students' motivation to study Biology between private schools in urban and rural areas. A quantitative approach with a comparative design was used in this study, involving 47 private high school students in Malang City as a representation of the urban areas and 37 private high school students in Malang Regency as a representation of rural areas. The research instrument was a closed questionnaire consisting of 31 statements reflecting the five dimensions of learning motivation: perseverance, tenacity, interest, achievement, and independence. Data were analyzed using descriptive statistics to see an overview of student motivation and the Mann-Whitney U test to test for significant differences between the two groups. The descriptive analysis results showed that students' mean motivation in urban areas was higher (4.56) than in rural areas (3.96). The standard deviation of urban students (0.57) was lower than that of rural students (0.65), indicating a smaller score variation. The Mann-Whitney U test showed a significant difference in motivation between the two groups. The results of this study confirm that students' learning motivation in urban private schools is higher compared to students in rural areas, which differences may influence educational facilities, access to learning resources, and environmental support. The findings are expected to serve as a basis for policymakers to design interventions to reduce the learning motivation gap between urban and rural areas.